The Corporate Governance Systems Transformation During the Financial Crisis - Bayura, D.O.; Romanyu, V.M. (Економічний вісник Донбасу, 2013)
This paper analyzes the stages of corporate governance development. It studies the issues and new challenges in the period of reform, transformation and convergence of modern corporate governance systems (models) that emerged in the context of the global economic crisis of 2008 - 2009. It demonstrates the causes of gradual accumulation of inefficiencies in large corporations operating in the global markets. The paper raises the need to find new forms of management for large businesses. In this context, we describe the strengths and weaknesses of corporate management in Ukrainian companies.